Comportamiento agronómico de una plantación de Copaifera paupera “Copaiba” y calidad de la oleoresina Zungarococha Iquitos - Villacrés Vallejo, Jorge Ysaac (2025)
The study was carried out at the Faculty of Agronomy - National University of the Peruvian Amazon (Zungarococha), where two areas of Copaifera paupera (Herzog) Dwyer were installed in 2009 with plants from Botanical Propagation (Seeds) and Natural Regeneration (Seedlings) and the height of plants was evaluated for 13 years (2010 - 2022). Chest (DBH) for 10 years (2013 – 2022), phenological stages and the chemical composition of the stem oleoresin. They began to be evaluated from the first year of age, initially considering the height of plants (m) and in the third year the Diameter at Breast Height. The evaluations were carried out annually using winches, clinometer, verniers and the analysis of the oleoresin by gas chromatography coupled to a mass detector (GC System model 7890B, MSD 5977B, Agilent Technologies). Regarding the percentage of germination, germination energy and vigor index, these were low in the three substrates used; while the plant height and Diameter at Breast Height (DBH) for Botanical propagation and Natural regeneration achieved similar heights in 13 years, achieving 10.27 and 10.07 meters and 22.02 and 22.38 cm respectively. In Botanical Propagation plants, 39 compounds were registered, highlighting Caryophyllene with 33.8% and in Natural Regeneration, 50 compounds where caryophyllene is lower with 28.9%. In both treatments, other major compounds were found such as Naphthalene with 9.281 and 9.332, Cyclohexane with 8.816 and 10.096, β bisabolene with 8.666 and 9.332% and α-cubebene with 4.177 and 4.825% respectively. The beginning of flowering occurs at 9 years of age in Natural Regeneration plants. Similarity in growth and diameter and a difference in the chemical composition of the oleoresin and initiation of flowering were found in both treatments.